What Object-Oriented Programming May Be: - and What It Does Not Have to Be - Madsen, Ole Lehrmann; Møller-Pedersen, Birger (DAIMI Report Series, 1989)
A conceptual framework for object-oriented programming is presented. The framework is independent of specific programming language constructs. It is illustrated how this framework is reflected in an object-oriented language and the language mechanisms are compared with the corresponding elements of other object-oriented languages. Main issues of object-oriented programming are considered on the basis of the framework presented here.